Photosynthesis and Photorespiration- I. Their roles in Yield and of Stress Resistance of C3 Crop Plants - André, Marcel J. (International Journal of Bio-resource and Stress Management, 2023)
The quantitative and functional relationships between Photosynthesis (P) and Photorespiration (PR) are illustrated from the data and the modelling of exchanges obtained by mass spectrometry techniques and 18O2 labelling. A brief history of oxygen and the roles of PR on plant evolution and at the present time, is reviewed. The function of a ‘mirror effect’ in the regulation between carboxylation and oxygenation cycles is underlined, in particular to mimic the effect of stomata and mesophyll regulation. Another function of regulation, under saturated light is underlined. The fitting of P and PR exchanges by a simple model allows the definition of the Plant Specificity factor for CO2 (Sp), directly determining the photosynthetic yield and the response of P and PR to CO2 and O2 concentrations. It is the sum of the biochemical Rubisco specificity and a biophysical specificity related to the conductances to CO2 diffusion. Their relative importance in the photosynthetic yield is emphasized. The constancy of Sp under different photosynthetic regimes implies a regulation of internal CO2 maintaining a constant ratio P/PR.